Kebijakan Penanganan Internally Displaced Persons (IDPs) di Indonesia dan Dunia Internasional - Susetyo, Heru (UI Scholars Hub, 2004)
In Indonesia, the concept of Internally Displaced Persons (IDPs) has not obvious enough and become the basis of thought yet. It can be seen from the regulation that regulate the IDPs which none of those regulations uses IDPs terminology. Another provides evidence is no regulation in act level regarding IDPs. The best regulation regarding IDPs in Indonesia is Presidential Decree Number 3 year 2001. The consequence of this condition, IDPs problems could not handle properly. Contrary condition with International, there are several instruments can be apply to resolve the IDPs problem such as the 1951 Refugee Convention, the 1949 Geneva Convention relative to the Protection of Civilian Persons in Time of War, The Second Additional Protocol 1977. The protection of victims of non-international armed conflicts, and The Guiding Principles on Internal Displacement (Guiding Principles). International bodies dealing with IDPs, like UNHCR could not directly access IDPs in Indonesia because of state sovereignty. This article is trying to provide the big picture of IDPs condition and the policy in Indonesia relating to the international law.